PELAKSANAAN REGULASI SISTEM STASIUN JARINGAN KOMPAS TV DEWATA - Krisna Arsani, Cok. Istri Ari; Amanda Gelgel, Ni Made Ras; Alit Suryawati, I Gusti Agung (E-Jurnal Medium, 2017)
The existence of centralization in the Indonesian television industry made the government try to make equity or decentralization to the broadcasting system by establishing policy for all broadcasting institutions in Indonesia to conduct a networking broadcasting system arranged in UU No.32 of 2002, PP No.50 of 2005, Kepmen Kominfo No. 43 of 2009, and P3SPS. The implementation of the network station system is intended to realize the decentralization and democratization of the broadcasting in Indonesia through the diversity of ownership and diversity of content. Kompas TV Dewata is one of the networked television stations that cooperate with local television stations in Bali. This research aims to determine the implementation of regulation of network station system conducted by Kompas TV Dewata in particular related to the broadcasting of local broadcast through analysis of mass media management. The results obtained are the implementation of regulation in Kompas TV Dewata very influenced by mass media management in the television station. The policy issued by Kompas TV Center as the largest shareholder impacted on the decrease in the duration as well as the quality of broadcasting of local broadcast programs. This makes the Kompas TV Dewata has not been able to implement the network station system to the maximum in accordance with the rules that apply, even the management of mass media in Kompas TV Dewata also very influenced by the policy of Kompas TV center.   Key Words : Kompas TV Dewata, Mass Media Management, Network Station System, Regulation.